2008
DOI: 10.1152/japplphysiol.00052.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin deficiency on postnatal lung development in mice

Abstract: Leptin modulates energy metabolism and lung development. We hypothesize that the effects of leptin on postnatal lung development are volume dependent from 2 to 10 wk of age and are independent of hypometabolism associated with leptin deficiency. To test the hypotheses, effects of leptin deficiency on lung maturation were characterized in age groups of C57BL/6J mice with varying Lep(ob) genotypes. Quasi-static pressure-volume curves and respiratory impedance measurements were performed to profile differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 56 publications
(71 reference statements)
1
47
0
Order By: Relevance
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 96%
“…Hypercapnic OSA patients have significantly lower hypercapnic ventilatory response when compared to eucapnic OSA patients with similar leptin levels [56]. Consequently, in humans with OHS, Leptin resistance is thought to contribute to the pathophysiology in a manner similar to that described in a leptin-deficient mouse model manifested by reduction in lung volumes, compliance, abnormal respiratory muscle function, and defects in upper airway neuromechanical control [17] [61,62].…”
Section: Leptin Resistance and Ohsmentioning
confidence: 99%
“…Increased levels of serum leptin have been shown to be associated with asthma in obesity, and related to airway reactivity 19,20 . The deficiency of leptin may also be associated with a reduced lung volume and lesser availability of alveolar surface to facilitate gas exchange 21 . Importantly, an increased expression of leptin and adiponectin in lungs and adipose tissue of obese patients with asthma has been reported, and there was a significant correlation between leptin and airway hyper-responsiveness 22 .…”
Section: Inflammatory Link Betweenmentioning
confidence: 99%